Cultural considerations in the assessment of sensitivity in low-income caregivers in Ethiopia - Spinelli, Maria; Preti, Emanuele; Kassa, Temsegen Tadele; Asale, Moges Ayele; Goshu, Mulat Asnake; Tsega, Tigist Wuhib; Gezie, Abebaw Minaye; Fasolo, Mirco; Mesman, Judi (Frontiers in Psychology, 2023)
Background. Caregiver sensitivity is associated with positive child outcomes, and improving sensitivity is often the aim of parenting-directed interventions. However, sensitivity was conceptualized in Western cultures and its application in populations with different backgrounds is still limited. Objective. This study aimed to foster a contextualized cultural understanding of the meaning and nature of sensitivity by assessing the possibility of evaluating sensitivity in a low-income population living in Ethiopia and describing the nature of (in)sensitive parenting. Moreover, the associations between sensitivity and discipline, quality of environment, and individual characteristics was explored. Methods. Parental sensitivity was coded on naturalistic video-recorded observations of free interactions between 25 female primary caregivers and their children. Caregivers completed questionnaires on discipline strategies and level of satisfaction with the environment (access to basic needs, quality of house condition, community and family support, quality of learning opportunities and working condition). Results. The assesment of sensitivity in this population was possible, with caregivers showing the full range of sensitivity levels. A description of manifestations of sensitivity in this population is provided. A K-means cluster analyses evidenced that high sensitivity was associated with high satisfaction regarding housing conditions and family environment. No association between sensitivity and discipline emerged. Conclusions. Findings show the feasibility of assessing sensitivity in this sample. The descriptions of observed behaviors contribute to understanding culturally specific aspects of sensitivity to consider when assessing sensitivity in similar populations. The study provides cultural considerations and guidelines to inform the structure of culturally-based interventions to promote sensitive parenting in similar cultural and socio-economic situations.